2016
DOI: 10.1016/j.envpol.2015.12.022
|View full text |Cite
|
Sign up to set email alerts
|

The associations between birth weight and exposure to fine particulate matter (PM2.5) and its chemical constituents during pregnancy: A meta-analysis

Abstract: We performed this meta-analysis to estimate the associations of maternal exposure to PM2.5 and its chemical constituents with birth weight and to explore the sources of heterogeneity in regard to the findings of these associations. A total of 32 studies were identified by searching the MEDLINE, PUBMED, Embase, China Biological Medicine and Wanfang electronic databases before April 2015. We estimated the statistically significant associations of reduced birth weight (β = -15.9 g, 95% CI: -26.8, -5.0) and LBW (O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
129
3
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 201 publications
(150 citation statements)
references
References 51 publications
17
129
3
1
Order By: Relevance
“…A recent meta-analysis using results from a number of previous studies found that Zn, Ti, V, OC, NO 3 À , EC, K, NH 4 + , Si and S were associated with LBW. 34 In this study, we found Blacks, Asians and older mothers had trends for greater associations with some PM 2.5 constituents. These subgroups may live closer to monitoring stations than others or have the highest exposure to PM 2.5 and its particular constituents.…”
Section: Interpretation Of Findingsmentioning
confidence: 46%
See 1 more Smart Citation
“…A recent meta-analysis using results from a number of previous studies found that Zn, Ti, V, OC, NO 3 À , EC, K, NH 4 + , Si and S were associated with LBW. 34 In this study, we found Blacks, Asians and older mothers had trends for greater associations with some PM 2.5 constituents. These subgroups may live closer to monitoring stations than others or have the highest exposure to PM 2.5 and its particular constituents.…”
Section: Interpretation Of Findingsmentioning
confidence: 46%
“…found increased risk of term LBW associated with EC, Br, NH 4 + and other constituents in California. A recent meta‐analysis using results from a number of previous studies found that Zn, Ti, V, OC, NO 3 − , EC, K, NH 4 + , Si and S were associated with LBW …”
Section: Commentmentioning
confidence: 99%
“…The heterogeneity between the included studies may reflect differences in the study settings, study design, exposure assessment, constituents of PM, and confounder adjustment, which may influence the variation in exposure to air pollution and potentially cause different dose-response relationships. 46,47 In addition, we found that age was negatively associated with effect sizes of air pollution, which indicated that age might be an important source of heterogeneity between studies. The protective effect of age might be related to the different medication use between young age and elderly.…”
Section: 50mentioning
confidence: 73%
“…Genomic imprinting arises early in fetal development and it has been suggested that these epigenetic patterns may function as a biosensor for the impact of in utero environmental exposures (Hoyo et al 2009; Jirtle and Skinner 2007). In addition, imprinting plays an important role in fetal development and growth, a process that has been found to be disrupted by exposure to air pollutants (Dadvand et al 2013; Lamichhane et al 2015; Sapkota et al 2010; Stieb et al 2012; Sun et al 2016; Zhu et al 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Maternal exposure to ambient air pollution during fetal development has been associated with reduced fetal growth, even at exposure levels lower than National Ambient Air Quality Standards (Dadvand et al 2013; Lamichhane et al 2015; Sapkota et al 2010; Stieb et al 2012; Sun et al 2016; Zhu et al 2015). However, the underlying molecular mechanisms remain unknown.…”
Section: Introductionmentioning
confidence: 99%